O letramento geográfico nas escolas rurais: uma experiência cartográfica na Escola Municipal de Ensino Fundamental Santa Flora – Santa Maria, RS - Ries, Zuleika Maria da Silva (2018)
This paper aims to expose the importance of cartographic literacy in rural schools, as well as the benefits that it brings to the cognitive development of the child. We also seek to establish the role of the Geography teacher in the teaching of cartography so that the students have a greater mastery of geographic contents as well as development on other fronts as a greater development in the society in which they coexist. At the same time, we present a history of the rural schools, and the concept of the school model of the Landless Movement - MST - an odd movement in structuring and propagating this concept of school and teaching. Finally, we point out the need to work and develop geography as a priority, starting with cartographic literacy for the full development of learners. And, to better present the theory, an participant research was carried out in a rural school in the District of Santa Flora - Santa Maria, RS, where the author of this dissertation is part of the school staff as a teacher. Field research results in a better understanding of the space lived by the students and observes that the teaching of geography needs without amplified, since the students in one of the activities that consisted in working with the space orientation, showed a great deficit on the part of the students to orient themselves spatially. The other activities present good results in presenting the world view of the students, clearly distinguishing the rural space and urban space. In view of this, it should be emphasized that cartographic literacy is extremely important for the development of students, both within school walls and especially outside them.